Production of ethanol and clarification of apple juice by pectinase enzyme produced from Aspergillus terreus NCFT 4269.10 - Sethi, Bijay; Satpathy, Amrita; Tripathy, Subodh; Parida, Sidarth; Singdevsachan, Sameer Kumar; Behera, Bikash (International Journal of Biological Research, 2016)
Aspergillus terreus NCFT 4269.10 was evaluated by liquid static surface fermentation (LSSF), shaking fermentation (ShF) and solid state fermentation (SSF) for the production of pectinase. Among various substrates tested, banana peels supported maximum production of pectinase i.e. 1000 Â± 141.42 U/ml. The biomass of A. terreus was maximum with wheat bran (0.55Â±0.07g/50ml). Pectinase produced by A. terreus displayed higher specific activity when wheat bran was used as the sole source of carbon and energy. After successful fermentation, crude enzyme was purified to electrophoretic homogeneity with a specific activity of 1846.50 U/mg from an initial specific activity of 1282.05 U/mg. The cell free-dialyzed-enzyme containing 107100 U was purified to 1.44 fold with an overall enzyme yield of 35.70%.Immobilization study revealed that the production of pectinase was increased up to third cycle and decreased thereafter when further pectinase production was carried out by immobilized spores of A. terreus.